Characteristics and geographical distribution of syphilis among people with human immunodeficiency virus and the National Population in Republic of Korea - Yae Jee Baek; Seyoung Kim; Eunjung Lee; Boyoung Park; Oeuk Jeong; Jongtak Jung; Jun Yong Choi; Tae Hyong Kim (PLoS ONE, 2026)
Introduction The global incidence of syphilis has been increasing in recent years, with multiple factors contributing to this trend. Syphilis disproportionately affects specific populations. We aimed to evaluate trends in the incidence and geographical distribution of syphilis at the provincial level among people living with human immunodeficiency virus (PLWH) and the total population in Korea. Methods PLWH were enrolled from the Korea National Health Insurance Service Database. Early syphilis was defined as having an International Classification of Diseases, 10 th revision diagnostic code and the prescription codes for medications. Between 2014 and 2019, syphilis was designated as a nationally notifiable infectious disease, facilitating comprehensive data collection. We compared the number of syphilis cases in the total population and the PLWH cohort. The incidence rates of early syphilis were estimated using Poisson regression, complemented by provincial mapping among the national and PLWH populations. Results The prevalence of early syphilis among PLWH was 22.4%, with 58.6% occurring after HIV diagnosis. In the total population, primary syphilis accounted for 69.8% of early cases. The age distribution and regional epidemiology of syphilis among PLWH differed from those in the total population. HIV infection was associated with a 5.04-fold higher incidence rate of syphilis (Incidence rate ratio (IRR), 95% Confidence interval (CI): 5.04 [4.77–5.34]), and as the years elapsed, the incidence rate of syphilis increased by 14.5% (IRR, 95% CI: 1.15 [1.13–1.16]). Since 2015, the incidence of new syphilis cases has increased notably in the total population, whereas it remained relatively stable among PLWH, indicating that the absolute rate and trajectories differed from those of the national population. Conclusion Syphilis is prevalent among PLWH; however, the epidemiology differs from that of the national population. This highlights the need for multifaceted policies to prevent syphilis transmission.